Association of the CHA(2)DS(2)VASc Score with Acute Stent Thrombosis in Patients with an ST Elevation Myocardial Infarction Who Underwent a Primary Percutaneous Coronary Intervention - Tanık, Veysel Ozan (Med Princ Pract, 2019)
OBJECTIVE: In this study, we aimed to determine the predictive value of the CHA2DS2VASc score for acute stent thrombosis in patients with an ST elevation myocardial infarction treated with a primary percutaneous coronary intervention (pPCI). METHODS: This was a retrospective study conducted among 3,460 consecutive patients with STEMI who underwent a pPCI. The stent thrombosis was considered a definite or confirmed event in the presence of symptoms suggestive of acute coronary syndrome and angiographic confirmation of stent thrombosis based on the diagnostic guidelines of the Academic Research Consortium. The stent thrombosis was classified as acute if it developed within 24 h. RESULTS: The mean CHA2DS2VASc score was 3.29 ± 1.73 in the stent thrombosis group, whereas it was 2.06 ± 1.14 in the control group (p < 0.001). In multivariable logistic regression analysis, CHA2DS2VASc scores ≥ 4 were independently associat ed with acute stent thrombosis (OR = 1.64; 95% CI 1.54–1.71, p < 0.001). In a receiver operating characteristic curve analysis, the best cut-off value for the CHA2DS2VASc score was ≥4, with 60% sensitivity and 73% specificity. Of note, pa tients with a CHA2DS2VASc score of 4 had a 4.3 times higher risk of acute stent thrombosis compared to those with a CHA2DS2VASc score of 1. CONCLUSIONS: The CHA2DS2VASc score may be a significant independent predictor of acute stent thrombosis in patients with STEMI treated with a pPCI. Therefore, the CHA2DS2VASc score may be used to assess the risk of acute stent thrombosis in patients with STEMI following a pPCI.